Encephalitozoonosis in the Blue Fox Comparison Between the India-Ink Immuno-Reaction and the Indirect Fluorescent Antibody Test in Detecting Encephalitozoon Cuniculi Antibodies - Mohn, Svein Fredrik (Acta Vet Scand, 1982)
Sera from 32 foxes sampled at intervals varying from 20 to 70 days after oral inoculation with E. cuniculi spores were tested by the india-ink immunoreaction (IIR) and the indirect fluorescent antibody test (IFAT). Using the IFAT, antibodies were detected at low levels in sera sampled on days 20 and 29 post inoculation, whereas the IIR failed to reveal antibodies in the same sera. In sera sampled from day 35 until day 70 post inoculation, antibodies were detected by both tests, the IIR-titres reaching the magnitude of the IFAT-titres after about 50 days posit inoculation. In 14 sera sampled from foxes of at least 46 days of age and with signs of encephalitozoonosis, the tests gave almost identical results. Comparing IIR- and IFAT-determined antibody titres using E. cuniculi antigens of blue fox and rabbit origin in the test, the antigens seemed to be closely related, supporting the suggestion that the isolates are strains of the same microsporidian species.